2022
DOI: 10.2147/rru.s344369
|View full text |Cite
|
Sign up to set email alerts
|

Role and Training of the Bedside Surgeon in Robotic Surgery: A Survey Among French Urologists-in-Training

Abstract: Introduction Due to the development of robotic surgery, surgeons operating at the console are physically separated from the patient. They must rely on help from an assistant, also called bedside surgeon. This study aimed to investigate the habits and practices of French urologic residents when performing this role and to determine whether they expected specific training to qualify as bedside surgeons. Materials and Methods A web-based survey was sent to French urology r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Bedside assistance is frequently described as a stepping stone on the path to console surgeon [4][5][6]. Prior work has acknowledged the multiple skills required as an assistant, and learning curve analysis has suggested that 10-36 cases are required for proficient bedside assistance [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…Bedside assistance is frequently described as a stepping stone on the path to console surgeon [4][5][6]. Prior work has acknowledged the multiple skills required as an assistant, and learning curve analysis has suggested that 10-36 cases are required for proficient bedside assistance [2,7].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive RAS training program should include three basic components: theoretical knowledge, simulation, and bedside assist and console management. 23 Alongside learning these technical skills, successful robotic surgery also requires mastery of multiple nontechnical skills (NTS). All of these components will be discussed in detail below.…”
Section: Current State Of Robotic-assisted Surgery and Trainingmentioning
confidence: 99%
“…Preconsole training should ensure that trainees have a foundational knowledge of the robotic system and have participated in an adequate number of RAS cases as the bedside assistant. 23 As the bedside assistant, performance of critical tasks such as trocar placement, robot docking, efficient instrument exchange, lavage, and troubleshooting develop both technical and operational RAS skills. Bedside assisting also portends experience in active, direct communication with the console surgeon, as the bedside assist is often the sole person at the patient's side during the case and maintains visualization of the global operating field.…”
Section: Component 3: Bedside Assist and Console Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, training has become a topic under the spotlight, with growing importance day after day, also in urology. Although there are articles evaluating the quality of teaching in some countries, as well as the work conditions, the residents’ laparoscopic and robotics skills, and the use of social media for learning purposes [ 4 12 ], a global comprehensive and objective evaluation of ideal urological teaching is still lacking.…”
Section: Introductionmentioning
confidence: 99%